2020
DOI: 10.3390/ijerph17228653
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy Improves QTc Interval in Traumatic Brain Injury Patients

Abstract: Background: Traumatic brain injury (TBI) is commonly associated with cardiac dysfunction, which may be reflected by abnormal electrocardiograms (ECG) and/or contractility. TBI-related cardiac disorders depend on the type of cerebral injury, the region of brain damage and the severity of the intracranial hypertension. Decompressive craniectomy (DC) is commonly used to reduce intra-cranial hypertension (ICH). Although DC decreases ICH rapidly, its effect on ECG has not been systematically studied. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…iCEB has some degree of heart-rate dependency, meaning that iCEB, like the QT interval itself, should optimally be corrected for underlying heart rate. In a previous study, Dabrowski et al observed that ICEB values ​​were significantly higher in traumatic brain injury patients who underwent decompressive craniectomy who especially developed cardiac arrhythmia [ 33 ]. They suggested that the iCEB was relatively increased before decompressive craniectomy in patients who eventually experienced cardiac arrhythmias after decompressive craniectomy.…”
Section: Discussionmentioning
confidence: 99%
“…iCEB has some degree of heart-rate dependency, meaning that iCEB, like the QT interval itself, should optimally be corrected for underlying heart rate. In a previous study, Dabrowski et al observed that ICEB values ​​were significantly higher in traumatic brain injury patients who underwent decompressive craniectomy who especially developed cardiac arrhythmia [ 33 ]. They suggested that the iCEB was relatively increased before decompressive craniectomy in patients who eventually experienced cardiac arrhythmias after decompressive craniectomy.…”
Section: Discussionmentioning
confidence: 99%